Is the Indian Stock Market Affected by COVID-19? : Evidence from Cases or Fatalities - V., Veeravel; Karthikeyan, K.; Remiya, P. R. (Indian Journal of Research in Capital Markets, 2022)
This paper examined the impact of the coronavirus pandemic on the Indian stock market returns as influenced by the number of confirmed cases or death cases. The study used Bombay Stock Exchange (BSE) Sensex daily adjusted closing price, volume of trade, price to book ratio, market capitalization, and coronavirus-related control variables, namely daily total confirmed cases and daily total confirmed death cases between January 30, 2020 and December 08, 2020. Pooled Ordinary Least Square regression was employed to investigate the influence of the unprecedented pandemic on stock market returns. The results revealed that the stock market returns were influenced by both daily total confirmed cases and death cases. Also, it was established that the total confirmed cases positively affected the stock market returns; whereas, the total confirmed death cases negatively affected the market returns. However, to check the robustness of the results, the study employed bivariate regression analysis, which confirmed the results. Thus, it can be inferred that the results were unbiased.